Investigation of hydrogen storage on Sc/Ti-decorated novel B24N24. (27th November 2020) - Ma, Li-Juan; Rong, Yifei; Hao, Wenshu; Jia, Jianfeng; Wu, Hai-Shun
Abstract: Inspired by the TM−N4 coordination environment in single-atom catalysts, four novel TM-decorated B24 N24 (TM = Sc, Ti) fullerenes with six TM−N4 or TM−B4 units are designed. Molecular dynamic simulations confirm that the four TM6 B24 N24 fullerenes are thermodynamically stable. Their hydrogen storage properties were investigated using density functional theory calculations. Sc/Ti atoms bind to the N4 /B4 cavities with an average interaction energy of 6.30–11.96 eV. Hence, the problem of clustering can be avoided. 36H2 could be adsorbed with average hydrogen adsorption energies of 0.18–0.55 eV. The lowest hydrogen desorption temperatures at atmospheric pressure for Sc6 B24 N24 (N4 )–36H2, Sc6 B24 N24 (B4 )–36H2, Ti6 B24 N24 (N4 )–36H2, and Ti6 B24 N24 (B4 )–36H2 are 255 K, 318 K, 243 K, and 408 K, respectively. The maximum hydrogen gravimetric densities of the Sc6 B24 N24 and Ti6 B24 N24 systems are 7.74 wt% and 7.50 wt%, respectively. Therefore, the novel Sc6 B24 N24 and Ti6 B24 N24 could be suitable as potential hydrogen storage materials at ambient temperature. Graphical abstract: Image 1 Highlights: Four novel TM-decorated B24 N24 (TM = Sc, Ti) fullerenes are designed. MD simulations confirm the thermodynamic stability of the TM6B24 N24 fullerenes. The H2 gravimetric density of Sc6 B24 N24 and Ti6 B24 N24 are 7.74 wt% and 7.50 wt%. Hydrogen release begins at 243 K–408 K for TM6 B24 N24 –36H2.